Dietary Magnesium Intake Modifies the Association Between Vitamin D and Systolic Blood Pressure: Results From NHANES 2007–2014 - Huang, Weichao; Ma, Xiaoman; Chen, Yue; Zheng, Jiayi; Li, Haojia; Nizhamu, Ayinigaer; Hong, Qingting; Guo, Xuguang (Frontiers in Nutrition, 2022)
Abstract Introduction: Although the association between blood pressure and vitamin D has been well studied, the effects of dietary magnesium intake on this relationship are still unclear. Thus, this study aimed to determine the effects of dietary magnesium intake on the association between vitamin D and blood pressure. Research design and methods: The present study analyzed data from the continuous NHANES 2007-2014. We included 8799 participants aged 20 years or older. Multivariable linear regression was performed to assess the association between vitamin D and systolic blood pressure (SBP), diastolic blood pressure (DBP). Dietary magnesium intake was stratified by low magnesium intake (<299mg/d), high magnesium intake (>=299mg/d). Effect modification by dietary magnesium intake was assessed through interaction tests between vitamin D and SBP in the multivariable linear regression. Results: In this cross-sectional study, we found vitamin D was negatively related to SBP, but not to DBP. The relationship between vitamin D and SBP was different in the low and high magnesium intake group (β: -0.25 95%Cl: -0.4~0.07 vs β: -0.32 95%Cl: -0.52~ -0.12). Furthermore, magnesium intake significantly modified the negative relationship between vitamin D and SBP in most of the models. Conclusion: Our research showed that magnesium and vitamin D have an interactive effect in reducing SBP, which may have great importance for clinical medication.